ANALISIS PENERAPAN PROYEK PENGUATAN PROFIL PELAJAR PANCASILA DALAM MENGEMBANGKAN KECERDASAN INTRAPERSONAL PESERTA DIDIK DI SEKOLAH DASAR - Wida Rachmawati; Ahmad Hariandi; Silvina Noviyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to describe the implementation of the Pancasila Student Profile strengthening project in developing students' intrapersonal intelligence in elementary schools. The development process of intrapersonal intelligence is an important and fundamental capability as a reinforcement of students' character education. This research was conducted using a qualitative method with a phenomenological approach at SD Negeri 167/I Bulian Baru during the odd semester of the 2024/2025 academic year. The research subjects were the principal, teachers, and students. Research data collection was carried out through in-depth interviews (as primary data), observation, and documentation study (as supporting data). The collected data was then analyzed and validated using source triangulation and technique triangulation. The results showed that the implementation of the Pancasila Student Profile strengthening project at SD Negeri 167/I Bulian Baru was able to develop students' intrapersonal intelligence comprehensively through four stages: introduction, contextualization, real action, and reflection and follow-up, impacting the development of students' intrapersonal intelligence including the ability to understand oneself, manage emotions, self-reflect, make decisions, and adapt during the P5 program. The development process of students' intrapersonal intelligence was evident through various achievement indicators including increased self-awareness in environmental care, ability to manage emotions when working in groups, ability to reflect on behavioral impacts on the environment, responsible decision-making in waste management, and ability to adapt to changing habits towards sustainable lifestyles. From the research results, it can be concluded that the Pancasila Student Profile Strengthening Project (P5) contributes to the formation of environmental care character and significantly supports the development of intrapersonal intelligence aspects that are important for students' holistic development.